Intellectual Capital Toward Market Performance: Profitability as a Mediating and Maqashid Sharia as a Moderating Variable - Widyantono Arif; Amiruddin Amiruddin; Darmawati Darmawati; Muhammad Irdam Ferdiansah (Journal of Accounting and Investment, 2023)
Research aims: This study aims to determine the effect of intellectual capital on market performance with profitability as a mediating variable and the Maqashid Sharia Index (MSI) as a moderating variable in an empirical study of Indonesian Islamic banks.Design/Methodology/Approach: This research utilized descriptive quantitative and explanatory methods to explain the relationship between variables. The research population covered all Islamic commercial banks registered with Bank Indonesia (BI), totaling 14. Purposive sampling was applied to determine the research sample. This study employed both primary and secondary data sourced from the government’s published documents, comprising the annual reports and the financial statements of Islamic commercial banks from 2017 to 2019. Path analysis and Moderated Regression Analysis (MRA) were run to analyze the data.Research findings: In conclusion, all variables had a positive and significant relationship. The mediating variable significantly impacted the dependent variable, and the moderating variable also influenced the relationship between intellectual capital and market performance.Theoretical contribution/Originality: Well-managed intellectual capital could produce work efficiency, affecting the quality of individual performance and directly impacting company performance. Good profitability in the company could foster a high level of trust in investors, affecting the provision of capital and improving company performance. Maqashid sharia is crucial in making decisions, especially for Islamic banks; efficient decisions could improve company performance.